2021
DOI: 10.1177/15570851211062579
|View full text |Cite
|
Sign up to set email alerts
|

Severe and Pervasive? Consequences of Sexual Harassment for Graduate Students and their Title IX Report Outcomes

Abstract: Sexual harassment of graduate students is prevalent, yet little is known about their experiences reporting sexual harassment to their university. We conducted interviews with 32 graduate students who reported sexual harassment to Title IX to understand how survivors’ experiences of harassment align with report outcomes. Nearly all participants experienced severe, education-limiting consequences of the harassment and reported to ensure safety and restore educational access. Most reports were deemed unactionable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…One study analyzed the narratives of seven undergraduate survivors who reported to the Title IX office at their institution, finding that survivors faced minimization of sexual assault throughout the reporting process, lack of transparency and consistency in reporting procedures, and mistreatment from Title IX office staff (Holland & Cipriano, 2021). Another study of 32 graduate students across nine institutions found that Title IX investigation process outcomes (e.g., determinations that the harassment was not “severe” enough to constitute a policy violation) rarely reflected the severe negative consequences that survivors experienced (Cipriano et al, 2021). A study of 21 survivors at one institution found that survivors experienced negative outcomes as a result of participating in Title IX reporting processes (e.g., secondary victimization, and academic and financial consequences; Lorenz et al, 2022).…”
Section: Title IX and Institutional Responses To Sexual And Gender-ba...mentioning
confidence: 99%
“…One study analyzed the narratives of seven undergraduate survivors who reported to the Title IX office at their institution, finding that survivors faced minimization of sexual assault throughout the reporting process, lack of transparency and consistency in reporting procedures, and mistreatment from Title IX office staff (Holland & Cipriano, 2021). Another study of 32 graduate students across nine institutions found that Title IX investigation process outcomes (e.g., determinations that the harassment was not “severe” enough to constitute a policy violation) rarely reflected the severe negative consequences that survivors experienced (Cipriano et al, 2021). A study of 21 survivors at one institution found that survivors experienced negative outcomes as a result of participating in Title IX reporting processes (e.g., secondary victimization, and academic and financial consequences; Lorenz et al, 2022).…”
Section: Title IX and Institutional Responses To Sexual And Gender-ba...mentioning
confidence: 99%
“…(U.S. Department of Education, Office for Civil Rights, 2020, p. 30033). As such, behavior that might be perceived as harassing to many individuals on campus may not rise to the level of sexual harassment under Title IX (e.g., single event breast or buttock grabs: not pervasive; sexualized comments about a student's body: not severe) (see Cipriano et al, 2022;Richards & Rennison, 2022). As such, Richards et al (2014) suggests that "a consensual sex policy may function as a prudent extension to the sexual harassment policy or as a supplement to the existing policy so there is no gap in protection" (p. 340).…”
Section: Consensual Sexual Relationship Policiesmentioning
confidence: 99%
“…Additionally, the consequences imposed upon those who cause sexual harm under Title IX are less severe, which can benefit those who cause harm — while the maximum punishment in criminal courts is incarceration, the maximum punishment in Title IX processes is expulsion, with most people found responsible only facing suspension or disciplinary probation. Title IX is also one of the only laws that addresses certain types of sexual harassment — purposefully misgendering someone, for example, is not a criminal offense, but is a potential Title IX violation (Cipriano et al, 2021). Understanding Title IX’s effect on those who go through the process is thus crucial for understanding the full scope of how accountability systems affect survivors who seek recourse for a wide range of negative experiences.…”
Section: Background On School Sexual Violence and Title IXmentioning
confidence: 99%
“…Women and genderqueer students are especially vulnerable to experiencing sexual violence: studies have estimated from 20 to 28% of undergraduate women and 28 to 1 Department of Sociology, University of California, Irvine, CA, USA 38% of gender non-conforming undergraduate students in the U.S. experience sexual violence during their college years (Cantor et al, 2019;Hirsh & Khan, 2020;Mellins et al, 2017). Under Title IX, part of the Education Amendments Act of 1972, educational institutions have a legal obligation to have policies that address sexual and dating violence and give students access to accommodations (Cipriano et al, 2021). However, little previous research has addressed how students experience Title IX processes and whether perceptions of school bias alter student views of the process.…”
Section: Introductionmentioning
confidence: 99%